The High “Cost” of Experimental Drugs Obtained Through Health Litigation in Brazil - Silva, Ricardo Eccard da; Lima, Elisangela da Costa; Novaes, Maria Rita C. G.; Osorio-de-Castro, Claudia G. S. (Frontiers in Pharmacology, 2020)
Background: Brazilian patients have legal right to access unlicensed medicines undergoing clinical research if there is evidence of efficacy and safety. This study investigated the occurrence of serious adverse events related to very high-cost medicines from clinical studies, expanded access and compassionate use programs, obtained by patients though health litigation. Methods: A descriptive study using secondary data investigated unlicensed medicines obtained through lawsuits from 2010 to 2017, costing more than 1 million Brazilian reais (BRL), adjusted by the Brazilian Consumer Index to July 2017. Data sources were the Brazilian Health Surveillance Agency Registry (DATAVISA) and Adverse Events in Clinical Studies (NotivisaEC) Databases. Medicines were categorized by the Anatomical Therapeutic Chemical classification to level 03 and events by the WHO Adverse Drug Reaction Terminology. The study received ethical approval by the University of Brasilia Institutional Research Board. Results: In the period, 812 drugs were obtained through litigation, and of these, 78 exceeded cost of 1 million BRL; 44 of them presented reports of 1248 serious adverse events. Total Brazilian Government expenditure with these drugs was 3.2 billion BRL. Class L04A (n=7) showed greater expenditures (over 1.8 billion BRL). 196 deaths occurred and L01X was the most involved category (49.5%). Most other serious events (n=419) and sequelae (n=10) were related to L01X. Conclusion: Very high-cost drugs paid for by the government and obtained through health litigation presented deaths and serious adverse events in expanded access and compassionate use programs in Brazil.